Taiwanese Mathematical Olympiad 2002

Algebra Level 5

a 1 2 + a 2 3 + + a 2002 2003 = 4 3 a 1 3 + a 2 4 + + a 2002 2004 = 4 5 a 1 2003 + a 2 2004 + + a 2002 4004 = 4 4005 \begin{aligned} \dfrac{a_{1}}{2} + \dfrac{a_{2}}{3} + \cdots + \dfrac{a_{2002}}{2003} &= \dfrac{4}{3}\\\\ \dfrac{a_{1}}{3} + \dfrac{a_{2}}{4} + \cdots + \dfrac{a_{2002}}{2004} &= \dfrac{4}{5}\\ & \vdots\\ \dfrac{a_{1}}{2003} + \dfrac{a_{2}}{2004} + \cdots + \dfrac{a_{2002}}{4004} &= \dfrac{4}{4005} \end{aligned}

Given that real numbers a 1 , a 2 , , a 2002 a_1, a_2, \ldots, a_{2002} satisfy the system of equations above, evaluate the following sum: a 1 3 + a 2 5 + + a 2002 4005 . \dfrac{a_1}{3} + \dfrac{a_2}{5} + \cdots + \dfrac{a_{2002}}{4005}.

If your answer is of the form m n \dfrac{m}{n} , where m m and n n are coprime positive integers, submit m + n m+n .


The answer is 32080049.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Calvin Lin Staff
Dec 27, 2016

Given those real numbers, consider the rational polynomial

a i x + i 4 2 x + 1 \sum \frac{ a_i } { x + i } - \frac{ 4 } { 2x + 1 }

If we clear denominators, we get the polynomial:

( ( 2 x + 1 ) a i j i ( x + j ) ) 4 ( x + j ) \sum \left( (2x+1) a_i \prod_{j \neq i } ( x + j ) \right) - 4 \prod (x + j )

which is a degree at most 2002 polynomial. Since it has at most 2002 roots, and we already found 2002 roots of the form x = 1 , 2 , , 2002 x = 1, 2, \ldots, 2002 , thus we have the identity.

( ( 2 x + 1 ) a i j i ( x + j ) ) 4 ( x + j ) = C ( x 1 ) ( x 2 ) ( x 2002 ) \sum \left( (2x+1) a_i \prod_{j \neq i } ( x + j ) \right) - 4 \prod (x + j ) = C (x-1)(x-2) \ldots ( x - 2002 )

It remains to determine C C . Substituting in x = 1 2 x= - \frac{1}{2} , we get that 4 ( 1 2 + j ) = C ( 1 2 j ) -4 \prod ( - \frac{1}{2} + j) = C \prod ( - \frac{1}{2} - j ) , or that C = 4 4005 C = \frac{ - 4 } { 4005 } .

Finally, substituting in x = 1 2 x= \frac{1}{2} , we get

( 2 a i j i ( 1 2 + j ) ) 4 ( 1 2 + j ) = 4 4005 ( 1 2 1 ) ( 1 2 2 ) ( 1 2 2002 ) \sum \left( 2 a_i \prod_{j \neq i } ( \frac{1}{2} + j ) \right) - 4 \prod (\frac{1}{2} + j ) = \frac{-4}{4005} (\frac{1}{2}-1)(\frac{1}{2}-2) \ldots (\frac{1}{2} - 2002 )

Dividing throughout by ( 1 2 + j ) \prod ( \frac{1}{2} + j ) , we obtain

a i 1 2 + i = 2 2 200 5 2 \sum \frac{ a_i}{ \frac{1}{2} + i } = 2 - \frac{2}{ 2005^2 }

Dividing by 2, we thus get

a 1 3 + a 2 5 + + a 2002 4005 = 1 1 200 5 2 = 4020024 4020025 \frac{a_1}{ 3} + \frac{a_2} { 5 } + \ldots + \frac{a_{2002} } { 4005 } = 1 - \frac{1} { 2005^2 } = \frac{ 4020024 } { 4020025 }

Welp, carelessness claimed 2 hrs of my time.

Julian Poon - 4 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...